Pāratiyum Pārata tēcamum - Pāratiyār, 1882-1921 (Vāṉati Patippakam, 1979)
On India as represented in the writings of C. Subrahmanya Bharati, 1882-1921, Tamil poet and freedom fighter; includes a selection from his poetry and prose writings.